Two Spanish Masterpieces. A Celebration of the Life and Work of María Rosa Lida de Malkiel, ed. Pablo Ancos y Ivy A. Corfis, Nueva York, Hispanic Seminary of Medieval Studies, 2013 - Millán, Silvia (Celestinesca, 2021)
N/A